Optimization with Crashing Method and Linear Programming Application on Type 36 Housing Projects - Iq'bal Khairul Amar, Tsulis; Nurcahyo, Adi; Jenar Bagaskara, Gilang; Safta Wijaya, Arif (ASTONJADRO, 2023)
The growth of housing in Indonesia has been very significant in recent years.   The most found type of house is type 36. One of the areas with high purchasing power for housing is the Kendal Regency, which became the object of this study. Often housing projects experience delays caused by internal and external factors that can interfere with the duration of the initial planning. The effort that can be made to maintain the level of progress of the project is by acceleration. The optimal cost of the project due to the reduction in duration can be completed by acceleration techniques (Crashing) as linear programming models.   In this study, Crashing and Linear Programming methods were chosen to optimize the value of adding costs to accelerate three samples of housing. Housing A, Housing B, and Housing C. The data collected is in the form of RAB, scheduling, and other supporting documents. Linear programming in this study using LINDO software. The plan to accelerate the construction of type 36 housing is carried out using alternative overtime working hours, adding 1, 2 and 4 working hours on critical activities of each project. The optimum time is selected based on the smallest cost slope value from the program crashing calculation. The result is shown that in housing A the most optimal addition was 2 hours of overtime with a total extra cost of Rp.   54,643,600 and a total acceleration of 15 days. In housing B, the optimum value of time and cost is by adding 4 hours of overtime with a total additional cost of Rp.   21,644,140 with a 27-day acceleration. In housing C, the development optimizes by adding 4 hours of overtime at an additional cost of Rp.   74,587,900 with a 29-day acceleration.